Altered Regional Cortical Brain Activity in Healthy Subjects After Sleep Deprivation: A Functional Magnetic Resonance Imaging Study - Chen, Lingling; Qi, Xueliang; Zheng, Jiyong (Frontiers in Neurology, 2018)
Objective: To investigate acute sleep deprivation (SD)-related regional brain activity changes and their relationships with behavioral performances. Methods: Twenty-two female subjects underwent MRI scan and attention network test at rested wakefulness (RW) status and after 24-hours SD status. Amplitude of low-frequency fluctuation (ALFF) was used to inverstigate the SD-related regional brain activity changes. We used receiver operating characteristic (ROC) curve to evaluate the ability of those ALFF differences in regional brain areas to distinguish the SD status from the RW status, and we used pearson correlations to evaluate the relationships between those ALFF differences in brain areas and behavioral performances during the SD status. Results: Subjects at SD status exhibited lower accuracy rate and longer reaction time relative to RW status. Compared with RW, SD showed significant lower ALFF values in the right cerebellum anterior lobe, and higher ALFF areas in the bilateral inferior occipital gyrus, left thalamus, left insula, and bilateral postcentral gyrus. The area under the curve values of those specific ALFF differences in brain areas were (mean±std, 0.851±0.045; 0.805~0.93). Further ROC curve analysis demonstrated that the ALFF differences in those regional brain areas alone discriminated the SD status from the RW status with high degree of sensitivities (82.16%±7.61%; 75%~93.8%) and specificities (81.23%±11.39%; 62.5%~93.7%). Accuracy rate showed negative correlations with the left inferior occipital gyrus, left thalamus and left postcentral gyrus, and showed a positive correlation with the right cerebellum. Conclusions: The ALFF analysis is a potential indicator for detection of excitation-inhibition imbalance of regional cortical activations disturbed by acute SD with high performances.